The Cost of Living Remotely: Long Distance Travel Associated with Overutilization of Chest Radiography Following Thoracic Surgery - Porter, Eleah D; Trooboff, Spencer W; Sacks, Olivia A; Fay, Kayla A; Hasson, Rian M; Millington, Timothy M; Finley, David J; Phillips, Joseph D (Archives of Clinical and Biomedical Research, 2021)
Background: Healthcare overutilization is a crisis in the US. We sought to investigate if travel distance and/or other perioperative factors were associated with the ordering of unnecessary pre-discharge chest x-rays in thoracic surgery patients at a rural institution. Methods: This was a retrospective cohort study of adults admitted after undergoing thoracic surgery with a chest tube placed at a rural, academic center. Prior to discharge, all patients underwent a standard single post-chest tube removal chest x-ray. Our primary outcome was the incidence of an unnecessary repeat (more than the standard one) chest x-ray in an asymptomatic patient. Our primary exposure was travel distance (driving distance from home zip code to hospital), dichotomized at 50 miles (short vs. long). A multivariable analysis was performed to identify if travel distance or other factors were associated with undergoing an unnecessary repeat chest x-ray. Results: Of 241 included patients; 155 (64%) traveled long distance and 86 (36%) traveled short distance. There were no preoperative differences between patients. On multivariable analysis, long distance travel increased the odds of undergoing an unnecessary repeat chest x-ray by almost three-fold compared to short distance travel (Odds Ratio: 2.80, 95% Confidence Interval: 1.32-5.97). A patient’s rural designation, the operating surgeon, and having a postoperative complication were also independently associated with this unnecessary chest x-ray. Conclusions: Long distance travel independently increased the odds of a thoracic surgery patient undergoing an unnecessary pre-discharge chest x-ray. Awareness of this overutilization may improve the efficiency of postoperative care pathways in rural settings.